Couples are Made of Four: Intergenerational Transmission of Within-household Allocations - Garcia-Brazales, Javier (ZBW - Leibniz Information Centre for Economics, Kiel, Hamburg, 2021)
There is increasing evidence in favor of non-unitary models of the household. Moreover, gender norms and values have been shown to be transmitted across generations and to affect intra-household allocations. I lever a unique opportunity to observe each spouse’s contributions to income, market, and home hours of parents and children (after forming their own household) in China and Australia to uncover a strong positive correlation between the female spouse’s relative contributions across two generations in the absence of reverse causality. This is robust to the inclusion of a rich vector of controls and provincial fixed effects. Exploiting large exogenous changes in education brought along by the Chinese 1986 Compulsory Education Law, I find that the degree of intergenerational transmission was disrupted by the reform, and that this happened heterogeneously across groups with different parental relative contributions. I further show that this was driven by a change in the attitudes towards gender norms, which suggests that transmission occurs at least partly through socialization and that policies can have a multiplier effect both within and across generations.
Keywords: Gender; Intergenerational transfer